HUBUNGAN PENGETAHUAN DAN SIKAP IBU DENGAN PEMBERIAN ASI EKLUSIF DI WILAYAH KERJA UPT PUSKESMAS MERAL KABUPATEN KARIMUN PROVINSI KEPULAUAN RIAU TAHUN 2018 - Mustafa, Darlaini; Ibrahim, Ibrahim (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2019)
Exclusive breastfeeding deals with breast milk feeding for the baby aged 1 day to 6 months old with no additional or complementary foods or drinks, except drugs, vitamins and minerals. The activity of exclusive breastfeeding done by the postpartum mothers in Riau Islands Province is quite small compared to the national realizations. Meral is noted to be the region with lowest percentage of infants’ exclusive breast feeding among other regions in Karimun in 2016 by the percentage of only 14.53%. The purpose of this study is to investigate the correlation of knowledge levels of postpartum mothers and their attitudes toward the exclusive breastfeeding for their baby particularly. This research used analytic survey method with cross sectional approach at the working area of Meral Health Center of Karimun conducted in April-June 2018.Thepopulation in this research 377 mothers and sample of 79 respondents selected by quota sampling technique with questionnaire instrument. The result of bivariate analysis using chi square with p value 0.004 (0.004<0.05) and p value 0.007 (0.007<0.05). The conclusion that there is a significant correlation between mother’s knowledge levels to do exclusive breastfeeding. Conversely, it is also confirmed that there is a significant correlation between their attitudes and exclusive breastfeeding for their baby. Therefore, it is hoped all parties to be more concerned about the importance of exclusive breastfeeding and to support the newborn mothers’ to do the exclusive breastfeeding for their baby.